Survival of Arcobacter butzleri and Arcobacter cryaerophilus strains in the presence of sea buckthorn extracts - Kučerová, Simona; Šilha, David; Vytřasová, Jarmila; Švecová, Blanka (My University, 2017)
Bacteria of the genus Arcobacter can be a cause of serious diseases not only for humans but also for animals. Therefore, their presence in food has to be eliminated. The strains of Arcobacter butzleri and A. cryaerophilus were used in this experiment as isolates, obtained from foodstuffs, and also as collection strains. The aim of this study was to test the survival of arcobacters in the presence of sea buckthorn (Hippophae rhamnoides L.) extracts (ethanolic extract from sea buckthorn, and extract from sea buckthorn in phosphate buffered saline). Antimicrobial sensitivity was tested by agar diffusion well test, followed by determination of minimum inhibitory concentration for individual extracts. To verify the inhibitory effect of the extracts, testing the antimicrobial effect of artificially inoculated foodstuff was carried out. Extracts were also analysed using high-performance liquid chromatography with diode-array detector, with the aim to approximately identify their substances. The results of this study show that sea buckthorn extracts could be suitable natural antimicrobial substances active, in particular against A. butzleri and A. cryaerophilus.
Přežívání kmenů Arcobacter butzleri a Arcobacter cryaerophilus v přítomnosti rakytníkového extraktu
Keywords: Arcobacter; sea buckthorn; natural extract; survival; Arcobacter; rakytník; přírodní extrakt; přežívání